2010
DOI: 10.1021/es1012577
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Induced Inactivation of Enteric Pathogenic Microorganisms with Ag−AgI/Al2O3 under Visible-Light Irradiation

Abstract: The plasmon-induced photocatalytic inactivation of enteric pathogenic microorganisms in water using Ag-AgI/Al(2)O(3) under visible-light irradiation was investigated. The catalyst was found to be highly effective at killing Shigella dysenteriae (S. dysenteriae), Escherichia coli (E. coli), and human rotavirus type 2 Wa (HRV-Wa). Its bactericidal efficiency was significantly enhanced by HCO(3)(-) and SO(4)(2-) ions, which are common in water, while phosphate had a slightly positive effect on the disinfection. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 26 publications
1
38
1
Order By: Relevance
“…coli and S. dysenteriae were inoculated into a nutrient broth medium, while S. typhimurium was maintained on tryptone soy broth (TSB) (Hu et al, 2010). HRV-Wa stocks were propagated, concentrated, and purified, using methods previously described by Jean et al (2002).…”
Section: Preparation and Enumeration Of Microorganismsmentioning
confidence: 99%
“…coli and S. dysenteriae were inoculated into a nutrient broth medium, while S. typhimurium was maintained on tryptone soy broth (TSB) (Hu et al, 2010). HRV-Wa stocks were propagated, concentrated, and purified, using methods previously described by Jean et al (2002).…”
Section: Preparation and Enumeration Of Microorganismsmentioning
confidence: 99%
“…Some researches showed that noble metal nanoparticles, such as Ag, Au and Pt, exhibited strong UV-vis absorption due to their plasmon resonance, which is produced by the collective oscillations of surface electrons [12][13][14][15][16]. Therefore, recently much more effort has been devoted to design Ag/AgX (X = Cl, Br, I) composite materials due to the surface plasmon resonance (SPR) of metallic Ag [1,[17][18][19][20], which can dramatically enhance the absorption of visible light (VL) and provide new opportunities to develop VLD photocatalysts [21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, complex composites formed by immobilizing Ag/AgX on inert supports [27][28][29] and magnetic Fe 2 O 3 [30] (Ag/AgX/suppport) or combining Ag/AgCl with other semiconductors (Ag/AgX/SC) [31] exhibited enhanced efficiency in photocatalytic degradation. In addition, these Ag/AgX/support and Ag/AgCl/SC composites also worked well in photocatalytic bactericide [32,33]. These indicate that Ag/AgXs play key roles in photocatalysis process both as a photocatalyst and a co-photocatalyst.…”
Section: Introductionmentioning
confidence: 71%